PENGARUH KEMUDAHAN PENGGUNAAN DAN RISIKO KEAMANAN TERHADAP MINAT PENGGUNAAN DOMPET DIGITAL DANA - Sundari, Siti; Rahmah Farhiyah (LPPM IAIT, 2025)
This study aims to determine the effect of ease of use and security risks on the interest in using the DANA digital wallet among students of the Islamic Economics Study Program, Tasikmalaya Islamic Institute. The background of this study is based on the increasing use of financial technology, especially digital wallets, which are considered practical and easy to use by the younger generation. The method used is quantitative with a multiple linear regression approach, processed using SPSS version 29. The study population was 111 students, and the sample used was 53 respondents selected using the simple random sampling technique. Data collection was carried out by distributing questionnaires, then analyzed using multiple linear regression tests, t-tests, f-tests, and coefficients of determination (R²). The results of the study indicate that both ease of use and security risks have a positive and significant effect on the interest in using the DANA digital wallet, both partially and simultaneously. This finding emphasizes the importance of developing a user-friendly interface and a reliable security system. This study can be input for application developers such as DANA to improve service quality, as well as for educational institutions in providing digital literacy to students.